(untitled) (Research, Society and Development, 2024)
This article aims to describe the process by which cultural and citizenship literacy is reinforced internally in the multicultural society of Baras Subdistrict, Pasangkayu Regency, Indonesia. The emphasis will be on the implications of this internalization for the formation, habituation, and reproduction of culture, with a particular emphasis on multicultural values. The unit of analysis for this qualitative descriptive study is the multicultural community residing in Baras Subdistrict, Pasangkayu Regency, Indonesia. The research subjects include several ethnic populations, including Javanese, Balinese, Buginese, Kaili, and local ethnic groups inhabiting rural parts of the Baras District. Methods of data collection include documentation, observation, interviews, and observation. This research employed the snowball sampling technique to acquire comprehensive information. The selection of informants is predicated on insights provided by community members and local authorities, including religious leaders, community leaders, and customary leaders. Techniques for data analysis encompass the steps of data reduction, interpretation, and conclusion. The results indicated that internalizing cultural and citizenship literacy reinforcement has been proceeding smoothly, as evidenced by the culture of cooperation and respect for one another among various ethnic communities. A correlation exists between cultural and citizenship literacy and the development of multicultural community behaviors that embrace diversity as a source of strength via familial, communal, and governmental influences.